ANALISIS YURIDIS TERHADAP KEBIJAKAN PEMUNGUTAN PAJAK Di INDONESIA - Agus Iskandar (KEADILAN PROGRESIF, 2021)
As a levy imposed by the state on the people, tax collection must be based on law. In carrying out its actions, state administration requires flexibility in determining policies related to tax collection. The problem in this research is how the government policies are related to tax collection. The method used in this research is descriptive analytical with a normative juridical approach, and a qualitative normative analysis method. The results show that the policies issued by the government in relation to the determination of taxes that must be issued by taxpayers which are determined in the form of tax collection are none other than those for general government financing purposes in order to carry out government functions, both routine and development. In fact, taxes are one of the largest state revenues. Revenue from the tax sector is then used by the